Os efeitos da lei nº 12.858/2013 na composição da receita dos beneficiários dos royalties: efeito 'nulo' no curto prazo versus migração no longo prazo - Cocchiarale, Yuri Barboza (2017)
The aim of this study is to show that the creation of the Law no. 12,858 / 2013 has an irrelevant effect in the short term, regarding issues related to health and education problems. By adopting some assumptions capable of modeling the obtained database and estimating oil production using the SARIMA, Holt-Winters and Kalman Filter models, combined with the price forecast, the portrayed results can consistently reflect the impacts brought by this law. The problem becomes even bigger in a long-term horizon, in which the migration of revenue from royalties will overwhelmingly affect the entities who benefit from it.